Inherited cultural capital and growth aspirations in Tanzanian business at the bottom of the pyramid. Issue 3 (3rd July 2021) - Lutz, Clemens; Noseleit, Florian; Tundui, Hawa
ABSTRACT: A large body of literature discusses the relationship between growth aspirations of small and medium-sized enterprise owners in emerging economies and the social capital and formal education of the entrepreneur. We argue that inherited cultural capital, rooted in the social background of the owner, is an additional important element to explain differences in growth aspirations, in particular for business owners at the bottom of the pyramid (BoP) in less developed countries. Our data confirm that different elements of inherited cultural capital do have a major influence on aspirations. The results suggest that this is related to the observation that small businesses operating at the BoP, in a weak institutional context, face difficulties in accessing social capital.